2012
DOI: 10.3892/mmr.2012.1153
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of hydrogen sulfide on oxidative stress and fibrosis in hepatic stellate cells

Abstract: In hepatic fibrosis, hepatic stellate cells (HSCs) are activated and change into myofibroblast-like cells which are characterized by increased proliferation and extracellular matrix (ECM) synthesis. In this study, we investigated the regulatory effects of hydrogen sulfide (H2S) on hepatic fibrosis. We detected the proliferation, cell cycle progression, apoptosis, intracellular reactive oxygen species (ROS) and free calcium levels in ferric nitrilotriacetate (Fe-NTA)-activated HSCs treated with sodium hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 22 publications
3
43
0
9
Order By: Relevance
“…The attenuation of fibrosis by H2S treatment is in concordance with literature showing decreased fibrosis in various organs following H2S exposure [46,[50][51][52]. STS outperformed NaHS with regard to decreased αSMA levels, which might be related to the lower level of interstitial macrophages in the former.…”
Section: Discussionsupporting
confidence: 89%
“…The attenuation of fibrosis by H2S treatment is in concordance with literature showing decreased fibrosis in various organs following H2S exposure [46,[50][51][52]. STS outperformed NaHS with regard to decreased αSMA levels, which might be related to the lower level of interstitial macrophages in the former.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our data, recent investigations showed that sodium hydrosulfide, a well-known inorganic H 2 S-releasing molecule, suppressed proliferation and induced G1 phase cell cycle arrest in HSCs [17] and attenuated collagen expression in rats with CCl 4 -induced hepatic fibrosis [18]. These findings collectively suggested H 2 S as a signaling molecule regulating the pathophysiology of HSCs.…”
Section: Discussionsupporting
confidence: 92%
“…Activation of these cells is induced by a variety of cytotoxic stimuli including oxidative stress and mitogenic and pro-inflammatory cytokines (Mallat and Lotersztajn 2013). In one study, exogenous H 2 S effectively inhibited the proliferation of stimulated rat hepatic stellate cells by reducing oxidative stress and increasing apoptosis in these cells (Fan et al 2013b). Clearance of activated hepatic stellate cells is essential for the regression of fibrosis (Mallat and Lotersztajn 2013).…”
Section: Cirrhosismentioning
confidence: 98%